Distance-decay patterns overshadow effects of long-term fertilization and tillage on microbial community structure in agricultural soils. Issue Volume 1(2019)Issue A (8th March 2019) - Brown, Claire; Helgason, Thorunn; Dytham, Calvin; Moir, James
Abstract : Community profiling is one of the most utilised tools in microbial ecology today. The relationships between microbial communities and their environment affect ecosystem function in fields spanning from medicine to agriculture; and understanding the community dynamics of a microbial community is key to understanding the complex effects of human intervention. In this study, we look at the effects of long-term tillage and fertilization regimes in soils from an agricultural block-designed field trial set up in 2001. By studying the microbial community composition, absolute microbial abundance and diversity of denitrification functional genes in the context of environmental data, we were able to address the question of how specific land management histories affect the diversity and distribution of bacteria and denitrification genes within agricultural soils. It was found that microbial communities appear to be largely unaffected by land management history, and cluster predominantly by spatial location within the field, despite lack of significant environmental variation. In this well-established agricultural field trial, Euclidean distance is the major identifiable determinant of microbial community dissimilarity (as well as dissimilarity in microbial abundance). That ecological drift, rather than physicochemical factors can be the major determinant of genetic potential may have consequences for attempts to understand nutrient availability in agricultural systems. Additionally, the overwhelming variation caused by spatial distance indicates that block designed experiments may not always have sufficient statistical power to identify any effects of human treatment.